ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL POLA BILANGAN TIPE HOTS (HIGHER ORDER THINKING SKILL) BERDASARKAN KEMAMPUAN MATEMATIKA KELAS VIII B SMP IT (ISLAM TERPADU) QURRATA A’YUN PALU - Yuyun; Awuy, Evie; Hasbi, Muh. (Universitas Tadulako, 2023)
This study aims to obtain a description of students' abilities in solving HOTS (Higher Order Thinking Skill) Type Number Pattern Problems Based on the Mathematics Ability of Class VIII B SMP IT (Integrated Islam) Qurrata A'yun Palu. This research is descriptive with a qualitative approach based on the problem-solving steps put forward by Polya. The results showed that subjects with high-level thinking skills and moderate-level thinking skills in solving mathematical problems with number patterns were as follows: (1) in understanding the problem, students with high-order thinking skills and moderate-level thinking skills demonstrated an understanding that was relevant to gathering information. The information contained in the problem can identify the problem of the problem with knowledge of the sentence